CULTIVATION OF OPTIMISTIC ATTITUDE TOWARDS LIFE OF A PERSONALITY AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM - Галина Карелова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with cultivation of optimistic attitude towards life of a personality as a psychological and pedagogical problem. It has been substantiated, that the works of psychologists and teachers of different epochs help you understand the concept of optimistic attitude towards life better, and that they are the methodological basis for the study of this phenomenon. Current understanding of optimism is based on cheerful attitude to the world, faith in our own human capabilities, success, in a better future.